COMMUNICATION STYLE OF USTADZAH HALIMAH ALAYDRUS IN THE “PURE HEART” GRAND STUDY - Najwa Nurhikmah; Isna Siskawati; Amin Sobar (Sekolah TInggi Ilmu Dakwa dan Komunikasi Islam (STIDKIS) Al Mardliyyah Pamekasa, 2025)
This study aims to examine the communication style used by Ustadzah Halimah Alaydrus in her da’wah (Islamic preaching) as well as to understand the meanings perceived by female congregants regarding the da’wah messages delivered during the grand study at Patriot Candrabhaga Stadium, Bekasi City, on May 12, 2025. The research employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, observations, and documentation. The analysis applied David K. Berlo’s SMCR (Source, Message, Channel, Receiver) theory, further expanded with the source components of ethos, logos, and pathos to illustrate the reciprocal interaction between the communicator (preacher) and the communicatees (congregants). The findings indicate that Ustadzah Halimah Alaydrus’s da’wah communication style is persuasive, gentle, and empathetic, facilitating the reception of da’wah messages among female congregants. Verbally, she emphasizes polite and logical language, while nonverbally she demonstrates calm facial expressions, harmonious body movements, and warm eye contact. The choice of a stadium as an open preaching venue provides a strong mass communication effect, accommodating thousands of congregants in a religious atmosphere despite being a non-religious public space. The meanings understood by female congregants include enhanced religious understanding, motivation for spiritual migration (hijrah), and the strengthening of modern Muslim women’s spirituality. Thus, Ustadzah Halimah Alaydrus’s communication style significantly influences the delivery of Islamic values in a humanistic, rational, and heartfelt manner